Implementasi Sistem Navigasi Terintegrasi untuk Pembuatan Petunjuk Jalan di Jalan Juma Gaja, Sikunihan 1, Sikunihan 2, dan Siboras - Damayanti Nababan; Andre Ari Wesly Sigalingging; Delima Sidabutar; Evelina Kristiani Simanjuntak; Reza Fahlevi Marbun; Rohana Simanjuntak (Pusat Riset dan Inovasi Nasional, 2024)
Road signs are visual or verbal information that provides road users with instructions or directions to help them reach their destination safely and efficiently. Traffic signs can be traffic signs, directional signs, road markings, or verbal instructions given by GPS navigation or road guidance. The purpose of directions is to provide clear information regarding direction, distance and travel route to the desired destination. The aim of this research is to develop effective guidelines for the Juma Gaja, Sikunihan 1, Sikunihan 2 and Siboras areas. By analyzing user needs and integrating GPS technology, we have designed a navigation system that can provide accurate and efficient directions. Field test methodology is used to ensure system effectiveness. The results show that the system implemented has succeeded in providing guidance that is timely and easy to use. The practical implication of this research is increasing mobility and transportation affordability in the study area..